Thyroid disorders and inflammatory bowel disease: an association present in adults but also in children and adolescents - Calcaterra, Valeria; Penagini, Francesca; Rossi, Virginia; Abbattista, Luisa; Bianchi, Alice; Turzi, Massimiliano; Cococcioni, Lucia; Zuccotti, Gianvincenzo (Frontiers in Endocrinology, 2025)
Inflammatory bowel diseases (IBD) represent chronic inflammatory multisystemic disorders that primarily involve the gastrointestinal tract. Patients with ulcerative colitis (UC) and Crohn’s disease (CD) exhibit a higher prevalence of thyroid disorders compared to the general population. The aim of this review is to summarize the literature on concomitant IBD and thyroid disorders, specifically autoimmune thyroid diseases such as Graves’ disease (GD) and Hashimoto’s thyroiditis (HT), as well as thyroid cancer, with a focus on children and adolescents. We provide an overview of the age-related differences between children and adults in the prevalence of this association. Literature shows that relatively few studies have been conducted on this subject in pediatric populations. The etiopathogenetic similarities between IBD and autoimmune thyroiditis are undeniable. Nevertheless, current data does not indicate a unanimous association between GD and HT and chronic IBD (both CD and UC). Although evidence suggests a potential association between IBD and thyroid cancer, particularly papillary thyroid cancer, the precise nature of this relationship varies across studies and is influenced by multiple factors. The limited information regarding the relationship between IBD and thyroid disorders in children highlights a significant knowledge gap. Since the thyroid plays a critical role in the pediatric population’s development, it is essential to promptly recognize and treat thyroid diseases. A thyroid function monitoring and future research exploring the genetic and immunologic connections are essential to enhance our understanding of the interrelation between IBD and thyroid disorders.